CO2 leakage from carbon dioxide capture and storage (CCS) systems affects organic matter cycling in surface marine sediments. (December 2016) - Rastelli, Eugenio; Corinaldesi, Cinzia; Dell'Anno, Antonio; Amaro, Teresa; Greco, Silvestro; Lo Martire, Marco; Carugati, Laura; Queirós, Ana M.; Widdicombe, Stephen; Danovaro, Roberto
Abstract: Carbon dioxide capture and storage (CCS), involving the injection of CO2 into the sub-seabed, is being promoted worldwide as a feasible option for reducing the anthropogenic CO2 emissions into the atmosphere. However, the effects on the marine ecosystems of potential CO2 leakages originating from these storage sites have only recently received scientific attention, and little information is available on the possible impacts of the resulting CO2 -enriched seawater plumes on the surrounding benthic ecosystem. In the present study, we conducted a 20-weeks mesocosm experiment exposing coastal sediments to CO2 -enriched seawater (at 5000 or 20, 000 ppm), to test the effects on the microbial enzymatic activities responsible for the decomposition and turnover of the sedimentary organic matter in surface sediments down to 15 cm depth. Our results indicate that the exposure to high-CO2 concentrations reduced significantly the enzymatic activities in the top 5 cm of sediments, but had no effects on subsurface sediment horizons (from 5 to 15 cm depth). In the surface sediments, both 5000 and 20, 000 ppm CO2 treatments determined a progressive decrease over time in the protein degradation (up to 80%). Conversely, the degradation rates of carbohydrates and organic phosphorous remained unaltered in the first 2 weeks, but decreased significantly (up to 50%) in the longer term when exposed at 20, 000 ppm of CO2 . Such effects were associated with a significant change in the composition of the biopolymeric carbon (due to the accumulation of proteins over time in sediments exposed to high-pCO2 treatments), and a significant decrease (∼20–50% at 5000 and 20, 000 ppm respectively) in nitrogen regeneration. We conclude that in areas immediately surrounding an active and long-lasting leak of CO2 from CCS reservoirs, organic matter cycling would be significantly impacted in the surface sediment layers. The evidence of negligible impacts on the deeper sediments should be considered with caution and further investigated simulating the intrusion of CO2 from a subsurface source, as occurring during real CO2 leakages from CCS sites. Highlights: CO2 leakages from CO2 capture and storage systems are unlikely, but still possible. The consequences on marine biogeochemical processes are almost completely unknown. We report significant decrease in sedimentary organic matter degradation rates. Surface and subsurface sediments respond differently to different pCO2 levels. CCS-induced CO2 leaks can have multifaceted effects on benthic marine ecosystems.